Pengaruh Gaya Kepempinan Partisipatif dan Nilai Nilai Perusahaan di Masa Pandemi Covid 19 Terhadap Kinerja Pegawai Melalui Komitmen Sebagai Variabel Intervening - Mhd Yecho Wijaya Ramadhan; Doni Permana; Syahrul Walidi; Andi Syahputra Batubara; Hafiz Abdillah; Safrida; Neni Sri Wahyuni; Sri Rahayu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research is based on the phenomenon of the covid-19 pandemic outbreak which has an impact on banking performance, therefore the authors formulate how to influence participatory leadership style and company values during the covid-19 pandemic on employee performance through commitment as an intervening variable at PT. Bank Mandiri (Persero) Medan Krakatau branch. This study aims to determine the effect of participatory leadership style during the Covid-19 pandemic on employee performance, the influence of corporate values on employee performance, the indirect influence of participatory leadership style during the Covid-19 pandemic through commitment to employee performance, the indirect effect of the value -company values during the covid-19 pandemic through commitment to employee performance. The population in this study are employees at PT. Bank Mandiri (Persero) Medan Krakatau branch as many as 172 people, the sampling technique used the slovin technique with a total of 64 people/sample. The analysis technique used is multiple linear analysis and path analysis. The results showed that participatory leadership style and company values affect employee performance. Participative leadership style through commitment does not directly affect employee performance and corporate values through commitment indirectly influence employee performance.